Analisa Kinerja Simpang Tak Bersinyal pada Jalan Ade Irma Suryani, Kecamatan Klojen Kota Malang - Pah Tuames, Maria Ursula ; Damar Pandulu, Galih ; Kristafi Arifianto, Andy (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The intersection is a point where various vehicles meet in a movement that is not the samedirection, so that the intersection occurs between the opposing road segments and causecongestion along the intersection arm. Likewise, at the Intersection of Jalan Ade Irma Suryani(West) - Jalan Sarif AL. Qoldir - Jalan Ade Irma Suryani (East) - KHWahid Street congestionoccurs due to reduced road width, parking lots on the road and street vendors (street vendors)which is along the body of the road. At the intersection of Jalan Ade Irma Suryani (West) -Jalan Sarif AL. Qoldir - Jalan Ade Irma Suryani (East) - Jalan K.H.Wahid there was acongestion caused by a side obstacle, which was not matched by adequate infrastructure. So thisresearch aims to analyze the performance of the unsignalized intersections based on the 1997Indonesian Road Capacity Manual (MKJI). In analyzing traffic capacity and behavior, field dataare needed in the form of: geometric conditions, traffic flow conditions for two weeks on June24, 2019 to July 7, 2019, with an observation time of 15 hours per day from 06:00 - 21:00 Wita.From the research, the current at peak hours of the first week occurs on Saturday, June 29, 2019at 3:00 - 16:00 West Indonesia Time. With a total vehicle volume of 15692 vehicles / hour or31384 pcu / hour and the current at peak hours of the second week occurs on Sunday, July 72019 at 16:00 - 17:00 Wita. With a total vehicle volume of 14832 vehicles / hour or 27664 pcu /hour. The calculation results show that the capacity of intersections (C) 2472,183 pcu / hour,with a degree of saturation (DS) of 1,329 pcu / hour, which means the degree of saturation thatoccurs ?0.75 of the required. Intersection delay (D) 23.24 seconds / junior high, and the chance of queuing (QP) that occurs is 150% - 78%. The conclusion that can be drawn is the capacity atthe intersection of Jalan Ade Irma Suryani, Klojen Subdistrict, Malang City, an improvementmust be made, namely by widening the road in the direction of Sarif AL.Qoldir street, JalanK.H.Wahid and making a sidewalk for pedestrians.